Djuna Barnes - Parsons, Deborah L. (Writers and Their Work Series., 2003)
In this illuminating and lucid study, Deborah Parsons examines the range of Djuna Barnes's oeuvre; her early journalism, short stories and one act dramas, poetry, the family chronicle Ryder, the Ladies Almanack, and her late play The Antiphon, as well as her modernist classic Nightwood.